1996
DOI: 10.1023/a:1016444808000
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The structural features of chitosans determining absorption enhancement are not correlated with those determining toxicity, which makes it possible to select chitosans with maximal effect on absorption and minimal toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(76 citation statements)
references
References 16 publications
2
74
0
Order By: Relevance
“…Toxicity was found to be degree of deacetylation and molecular weight dependent. At high DD the toxicity is related to the molecular weight and the concentration, at lower DD toxicity is less pronounced and less related to the molecular weight [93].…”
Section: Safe Biomaterialsmentioning
confidence: 96%
“…Toxicity was found to be degree of deacetylation and molecular weight dependent. At high DD the toxicity is related to the molecular weight and the concentration, at lower DD toxicity is less pronounced and less related to the molecular weight [93].…”
Section: Safe Biomaterialsmentioning
confidence: 96%
“…[11][12][13] It has also been reported that chitosan having a low degree of deacetylation (DA), which are active as absorption enhancer at both low and high molecular weights, shows a clear dose-dependent toxicity. 14) However, chitosan having a higher DA is active enhancer at high molecular weight, but show low toxicity at low molecular weight. As far as toxicity is concerned, it depends on the structural features of the chitosan polymer and not always related to its absorption enhancing effect.…”
Section: Propertiesmentioning
confidence: 99%
“…106,107) Chitosan solutions have shown to increase trans and para-cellular permeability in a reversible, dose-dependent manner depending on the molecular weight and degree of deacetylation of the chitosan. 108) The mechanism of action, which have been reported to be mediated by the positive charges on the chitosan, includes interactions with the tight junction proteins occludin and ZO-1, redistribution of F-actin, and slight destabilization of the plasma membrane. 107,109,110) This ability of chitosan to enhance permeation is also influenced by the pH of the environment.…”
Section: In Ocular Drug Deliverymentioning
confidence: 99%
“…It implies the NH 2 group or positive NH 2 group would be necessary for the inhibitory effect of glucosamine in vitro. A possible ionic interactions between the positively-charged NH 2 group in GlcNH 2 ⋅HCl and negatively-charged sialic acid residue on tumor cell surface would possibly result in a change in the ionic environment of the cell membrane, which is important in maintaining cell integrity and cell growth (Olsen et al, 1989;Santini et al, 1997;Schipper et al, 1996). Thus, it is the lack of the amino group in NAG (Chandy and Sharma, 1990).…”
Section: Discussionmentioning
confidence: 99%